MAKNA TANDA RAFA’ ALIF DAN HIKMAHNYA DALAM KEHIDUPAN UNTUK MENCAPAI KESUKSESAN - Putra, Mulya; Aqila Az Zahra, Nayyara (Yayasan Haiah Nusratul Islam, Indonesia, 2025)
This research focuses on one aspect of i'rab, namely the sign rafa' alif, which is not only grammatically meaningful but also holds deep symbolic and spiritual value. This study aims to uncover the meaning and wisdom behind the rafa' alif sign as reflected in the structure of the Arabic language and its application in life, especially as an inspiration to achieve true success. Using the descriptive content analysis method combined with Focus Group Discussion (FGD), this study analyzes the use of the letter